Pengkajian Agama secara Historis - Tarigan, Mardinal; Aprila, Gusti; Pratama, Riswanda (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
As we know that history cannot be separated from a series of events limited by the space and time in which the events occurred. Many people say that history is something static that cannot be repeated based on its context. Along with the development of human knowledge and the potential for great curiosity, it has influenced people's perspectives on history, which used to consider history as static, rigid, and even without any contribution to the advancement of scientific studies. However, this view has been shaken by the struggle of Islamic studies, where history is always dynamic, following the "pulse" of human civilization development. This article uses a heuristic method with critical analysis based on primary books, to dissect the uniqueness of the past that has a unique influence on the present and future. In this context, the effort to link the relevance of Islamic education as a field of life facing challenges is studied from various perspectives, including the historical perspective. At this point, the dynamism of Islamic education can mean developing scientific knowledge.